Analisis Bibliometrik: Pemetaan Penelitian Machine Learning dalam E-commerce Berdasarkan Data dari Scopus (2019-2024) - Yudhistira Arie Wijaya; Dadang Sudrajat (Prosiding SISFOTEK, 2024)
This study explores the application of machine learning in e-commerce using descriptive and visual bibliometric analysis methods. Data were collected from the Scopus database for the period 2019–2024 through five stages: defining search keywords, initial search results, refinement of the search results, compiling statistics on the initial data, and data analysis. The findings indicate a significant increase in publications from 2020 to 2023, peaking in 2023, followed by a decline in 2024. IEEE Access and the International Journal of Advanced Computer Science and Applications are the main sources of publications, with India and China standing out as the countries with the highest number of publications. International research collaboration shows significant growth, and co-word analysis identifies “machine learning” as a central topic closely linked with “electronic commerce” and “learning systems." Citation trends reveal that highly cited publications have a significant impact. These findings provide comprehensive insights into the development and contributions of research in machine learning for e-commerce, with important implications for researchers and industry practitioners in addressing new challenges and opportunities.